Hubungan Usia, Aktivitas Fisik, Kebiasaan Merokok, Dan Konsumsi Lemak Dengan Kejadian Hipertensi Pada Dewasa Usia 30-79 Tahun - nadia habibah; Sunarto; Kun Aristiati Susiloretni; Susi Tursilowati; Sri Noor Mintarsih (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2026)
Introduction: Hypertension is a leading cause of premature death worldwide, with only 21% of sufferers able to control the condition. Muktiharjo Kidul Village in Semarang City has the highest prevalence of hypertension in the Tlogosari Kulon Community Health Center (Puskesmas) coverage area. Objectives: This study aimed to analyze the relationship between age, physical activity, smoking habits, and fat consumption and the incidence of hypertension in adults aged 30–79 years. Methods: The study used an observational design with a cross-sectional approach. Results:the The results showed a significant association between age and physical activity with the incidence of hypertension. Those aged 50–64 years had a 2.9 times greater risk of developing hypertension compared to those aged 30–49 years (OR: 2.908; 95% CI: 1.061–7.969; p: 0.011), and those aged 65–80 years had a 5.7 times greater risk of developing hypertension compared to those aged 30–49 years (OR: 5.730; 95% CI: 1.770–18.550; p: 0.011). Light physical activity increases the risk of hypertension by 5.34 times compared to moderate and vigorous activity (OR: 5.341; 95% CI: 1.429–19.959; p: 0.007). There was no significant association between smoking (p: 0.07) and fat consumption (p: 0.676) and hypertension. Conclusions: This study concluded that there is a significant association between age and physical activity with the incidence of hypertension in adults aged 30-79 years in Muktiharjo Kidul Village.